Evaluating the energy dependence of various polystyrene based plastic scintillators. (March 2019) - Whittaker, Carly A.; Santos, Alexandre M.C.; Kalnins, Christopher A.G.; Ebendorff-Heidepriem, Heike; Ottaway, David; Spooner, Nigel A.
Abstract: Plastic scintillation detectors (PSDs) have been extensively tested as in-vivo dosimeters for brachytherapy dosimetry, but they are known to suffer from an energy dependence in low energy photon beams, an unwanted characteristic of any dosimeter. It has been demonstrated that the base material of the plastic scintillator can have a significant impact on the PSDs energy dependent behavior in x-ray beam voltages from 25 to 100kV P (Peralta and Rêgo, 2014). In this work, a comprehensive range of polystyrene based PSDs are studied to determine if the scintillator composition and geometry has any impact on their energy dependent behavior in superficial x-ray beams in the 30 to 150 kV P range. The relative response of each scintillator tested was found to vary by up to 77% across the 0.014–0.061 MeV effective energy range, with a maximum variation in relative response of 13.1% between the different scintillators. These results demonstrate the PSD diameter, formulation and cladding do not significantly impact the scintillator performance in the studied energy region. Highlights: The energy dependent response of 14 different plastic scintillating optical fibres have been tested in superficial x-ray beams between 30 and 150 Kvp. The relative response of the scintillators was found to vary by up to 77% in the 0.014–0.061 MeV effective energy range. There was found to be a maximum 13.1% variation in relative response between the different scintillators. The scintillator formulation, diameter and cladding have no significant effect on performance in the studied energy range.